Antecedents and Consequences of Bloggers Attitude to Consumer on Intention to Online Shop - Ulfa Oktavani Nasution; Vanisa Meifari; Nurfitri Zulaika; Tommy Munaf (Budapest International Research and Critics University, 2022)
This study to examine the antecedents and consequences of bloggers attitude which is believed to be one of the strategies of a company, organization towards the intention to shop online. Bloggers attitude is a variable to have an influence on how someone can want to buy a product and service that is offered. This research used Quantitative research methods with 95% confidence level. The data collection is conducted by distributing questionnaires. The sample was randomly selected with a total sample of 150 respondents from Master of Management students, especially Bloggers at Trisakti University, Jakarta. The data analysis technique used Structural Equation Modeling technique with SmartPLS application, to show that the effects of bloggers knowledge hypothesis on the bloggers attitude, bloggers market mavenism has an effect on bloggers attitude, bloggers responsiveness has an effect on bloggers attitude, bloggers social network optimization has an effect on bloggers attitude, trust has an effect on bloggers attitude, bloggers attitude affect the intention to shop online.